Cortical activity evoked by inoculation needle prick in infants up to one-year old. Issue 2 (February 2015) - Verriotis, Madeleine; Fabrizi, Lorenzo; Lee, Amy; Ledwidge, Sheryl; Meek, Judith; Fitzgerald, Maria
Abstract : Abstract: Inoculation is one of the first and most common experiences of procedural pain in infancy. However, little is known about how needle puncture pain is processed by the central nervous system in children. In this study, we describe for the first time the event-related activity in the infant brain during routine inoculation using electroencephalography. Fifteen healthy term-born infants aged 1 to 2 months (n = 12) or 12 months (n = 5) were studied in an outpatient clinic. Pain behavior was scored using the Modified Behavioral Pain Scale. A distinct inoculation event–related vertex potential, consisting of 2 late negative-positive complexes, was observable in single trials after needle contact with the skin. The amplitude of both negative-positive components was significantly greater in the 12-month group. Both inoculation event–related potential amplitude and behavioral pain scores increased with age but the 2 measures were not correlated with each other. These components are the first recordings of brain activity in response to real-life needle pain in infants up to a year old. They provide new evidence of postnatal nociceptive processing and, combined with more traditional behavioral pain scores, offer a potentially more sensitive measure for testing the efficacy of analgesic protocols in this age group. Abstract : Supplemental Digital Content is Available in the Text.Inoculation elicits a clearly defined cortical electroencephalography response in preverbal infants that increases in amplitude between 1 to 2 and 12 months of age.